A Place for Us? Baby Boomers, Their Elders, and the Public Library - Robbins, Wendy L. (Université d'Ottawa / University of Ottawa, 2012)
Canada’s aging population is expected to have an impact on all public institutions; for public libraries, the emergence of a large, multi-generational user group of older adults challenges the current paradigm of services to seniors. This thesis examines a subset of this user group: baby boomer library patrons who are in a caring relationship with elders. It investigates how these patrons interact with the public library both for themselves, and as carers, in order to reveal library-related issues particular to this growing segment of the population. The study takes place within a conceptual framework derived from the ethic of care, and from emerging theories of library-as-place rooted in the fields of human geography and sociology. Using a qualitative instrumental case study method, long form interviews were conducted with respondents recruited through theoretical sampling extended by snowball sampling. While not generalizable, findings suggest that while these baby boomer respondents value their libraries deeply, there is potential to create services and practices more attuned to the needs of older adults who are in relationships with elders.
Keywords: adult services; aging population; baby boomer; demographic change; elders; ethic of care; library as place; public libraries; seniors